The library dragon - Deedy, Carmen Agra.; White, Michael P. (Atlanta : Peachtree, 1994)
Miss Lotta Scales is a dragon who protects the school's library books from the children, but when she realizes the books are meant to be read, she turns into Miss Lotty, librarian and storyteller.
AD 690
Keywords: Librarians -- Fiction; Dragons -- Fiction; Libraries -- Fiction; Books and reading -- Fiction; School stories